2007
DOI: 10.1158/1078-0432.ccr-07-1579
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B Prevents Doxorubicin-Induced Cardiotoxicity via Enhancing Glutathione Redox Cycling

Abstract: Purpose: The dose-cumulative cardiotoxicties and the emerging cancerous apoptotic/drug resistance are two major obstacles limiting the efficacy of anthracycline antibiotics, notably doxorubicin. We attempted to prove if schisandrin B (Sch B), a dual inhibitor of P-glycoprotein and multidrug resistance^associated protein 1, could protect against doxorubicin-induced cardiotoxicity, on the premise that Sch B is an enhancer of glutathione redox cycling that may attenuate doxorubicin-induced oxidative stress in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 42 publications
4
32
0
Order By: Relevance
“…This communication, combined with our previous reports [13,16,17,18,22,23], provides evidence that Sch B can protect Dox-induced acute and chronic cardiotoxicity and enhancing its anticancer activity.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This communication, combined with our previous reports [13,16,17,18,22,23], provides evidence that Sch B can protect Dox-induced acute and chronic cardiotoxicity and enhancing its anticancer activity.…”
Section: Discussionsupporting
confidence: 78%
“…We have demonstrated that Sch B was a dual inhibitor of P-glycoprotein and multidrug-resistance associated protein, and thus could sensitize drug-resistant cells to many structurally and functionally unrelated drugs including anthracycline antibiotics as the substrates of the 2 drug pumps [13,16,17,18]. We also demonstrated that Sch B enhanced Dox anticancer activities in vivo against KBv200 (a human epidermoid carcinoma cell line overexpressing P-glycoprotein inoculated s.c. in nude mice) [19].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Further in in-vitro model Sch B elicits a glutathione antioxidant response and protects against apoptosis via the redox-sensitive ERK/Nrf2 pathway in AML12 heptocytes. (Leong, Chiu et al 2011) Sch B treatment increases antioxidant status of the heart and improves cardiac function against the adiramycin, doxorubicin and ischemia/reperfusion induced cardiac dysfunction (Li, Pan et al 2007;You, Pan et al 2006;Chiu and Ko 2004). It has been reported that Sch B enhances renal mitochondrial antioxidant status and protects against gentamicin-induced nephro-toxicity in rats.…”
Section: The Antioxidant Potential Of Sch B In Various Organsmentioning
confidence: 99%
“…The exact molecular mechanisms, however, in which reactive oxygen species (ROS) are considered to be central remain unclear (1,5). It was reported that Dox has been observed to transform into a semiquinone radical, which then reduces oxygen to produce superoxide and reacts with polyunsaturated fatty acids to yield lipid hydroperoxide (6). The antioxidants, which cleaved the generated ROS, were hypothesized to exhibit protective effects against Dox-induced cardiomyopathy (7,8).…”
Section: Introductionmentioning
confidence: 99%